Empowering Elderly Voters with Special Health Conditions in Pemecutan Kaja Village: Socialization and Education to Prevent Voter Abstention - Adyatna Wedananta, Kadek; Raihandi, Rizki (LPPM Universitas Jambi, 2024)
Elections are an important moment for every citizen to participate in determining the direction of governance. However, voter participation, especially among the elderly, faces significant challenges. In Indonesia, the low voter turnout, partly due to the phenomenon of